Determinants of earnings quality: An empirical study in Indonesia - Hairul Anam (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2023)
This study aims to investigate the factors that influence the quality of earnings. In this study, there are three independent variables: capital structure, investment opportunity set, and information asymmetries on earnings quality. Indicators of earnings quality are discretionary accruals. The capital structure will be expressed as a ratio of debt to equity. Comparing the investment opportunity set's market value to its book value allows for its evaluation. Information asymmetries are quantified using the bid-ask spread. The population studied utilizes the manufacturing sector. The method of determining a sample using the technique of purposive sampling. As many as 160 firm years were used to collect research samples that met the criteria. The analysis instrument employs multiple linear regression analysis techniques. According to the findings of the study, capital structure and asymmetric information have a positive impact on earnings quality. Moreover, the investment opportunity set has no effect on the quality of earnings.